Illumination/Darkness-Induced Changes in Leaf Surface Potential Linked With Kinetics of Ion Fluxes - Li, Jinhai; Yue, Yang; Wang, Ziyang; Zhou, Qiao; Fan, Lifeng; Chai, Zhiqiang; Song, Chao; Dong, Hongtu; Yan, Shixian; Gao, Xinyu; Xu, Qiang; Yao, Jiepeng; et al. (Frontiers in Plant Science, 2019)
A highly reproducible plant electrical signal–light-induced rhythmical bioelectrogenesis (LIRB) was obtained by means of periodic illumination/darkness stimulation of broad bean (Vicia faba.L) leaves. By stimulating the same position of the same leaf with different concentrations of NaCl, we observed that the amplitude and waveform of the LIRB was correlated with the intensity of stimulation. This method allowed us to link dynamic ion fluxes induced by periodic illumination/darkness to salt stress. The self-referencing ion electrode technique was used to explore the ionic mechanisms of the LIRB. Fluxes of H+, Ca2+, K+, and Cl− showed periodic changes under periodic illumination/darkness before and after 50 mM NaCl stimulation. Gray relational analysis was used to analyze correlations between each of these ions and LIRB. The results showed that different ions are involved in surface potential changes at different stages under periodic illumination/darkness. The gray relational grade reflected the contribution of each ion to the change in surface potential at a certain time period. The ion fluxes data obtained under periodic illumination/darkness stimulation will contribute to the future development of a dynamic model for interpretation of electrophysiological events in plant cells.